Calculation of S-parameters for network cascading and deembedding - Huang, Jiahan (Nanyang Technological University, 2022)
This dissertation report presents the calculation of S-parameters for network cascading and deembedding. The calculation methods can be formulated in two forms, i.e., based on matrix form and element form. In addition, the methods not only consider balanced networks and imbalanced networks, but also deal with the cases when the number of external ports is greater / less than the number of internal ports. After numerical tests and experiments, it is found that the methods based on matrix form may suffer from the problem of singular matrix. On the other hand, the method based on element form is effective, but it is not easy to be generalized and thus needs further optimization.